2023
DOI: 10.1111/inm.13134
|View full text |Cite
|
Sign up to set email alerts
|

Challenging stigma and attitudes towards ECT via an educational video

Abstract: While electroconvulsive therapy (ECT) is an effective therapeutic modality for the treatment of mental illness, negative attitudes and stigma exist about ECT in the general community and even within health services. Investigating interventions that improve the attitudes of health professionals towards ECT is beneficial as this reduces stigma and increases the acceptability of ECT for consumers. The primary aim of this study was to evaluate the change in attitude of nursing graduates and medical students toward… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…The previous studies found that the media in general is an essential source of information for patients and their primary caregivers, but how valuable and reliable it is contested. 6,7 In recent years, the number of health-related videos on YouTube has increased. 8 Therefore, most patients and their primary caregivers seek advice and information related to ECT by using the YouTube platform, and that can have a significant impact on their behaviors and decisions.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The previous studies found that the media in general is an essential source of information for patients and their primary caregivers, but how valuable and reliable it is contested. 6,7 In recent years, the number of health-related videos on YouTube has increased. 8 Therefore, most patients and their primary caregivers seek advice and information related to ECT by using the YouTube platform, and that can have a significant impact on their behaviors and decisions.…”
mentioning
confidence: 99%
“…Thus, to overcome the previous factors, the patients and their primary caregivers should find another supportive source, such as YouTube, to gain information related to electroconvulsive therapy, plus information from healthcare providers. The previous studies found that the media in general is an essential source of information for patients and their primary caregivers, but how valuable and reliable it is contested 6,7 …”
mentioning
confidence: 99%